Composition of essential oil two medicinal plants (Eucalyptus camaldulensis dehnh. and vibirnum opulus l.) - Doğan, Gülden; Akbaba, Emel; Kılıç, Ömer (My University, 2017)
Eucalyptus is one of the world’s important and most widely planted species belongs to the family Myrtaceae. Several species of Eucalyptus are used in folk medicine as an antiseptic and against infections of the upper respiratory tract, such as cold, influenza and sinus congestion. The essential oil of Eucalyptus species showed a wide spectrum of antimicrobial, antifungal, anticandidal, antibacterial, expectorant and cough stimulant activity. In this study, the chemical composition of the essential oil from the leaves and fruits of Eucalyptus camaldulensis Dehnh. and aerial parts of Vibirnum opulus L. grown in Mersin (Turkey) were analyzed by using GC and GC/MS techniques. The yields of essential oils were 1.2% in leaf and 1.0% (v/w) in fruit of E. camaldulensis and identified representing 93.8% and 99.0% of the total oils, respectively. The major constituents of leaves were p-cymene (42.1%), eucalyptol (1,8-cineole, - -terpinol (10.7%), and in fruit were eucalyptol (1,8 cineole) (34.5%), p- -terpinol (15.1%). Our results showed that both oils has rich in terms of monoterpene hydrocarbons and oxygenated monoterpenes. Viburnum opulus is from Adoxaceae family and it is reported that has anticancer, antiaging and antioxidant activity. This species used for renal stone reduction. The yields of essential oil of V. opulus was 0.5% - - pinene (27.2%) and butanoic acid (15.8%) were the main compounds identified in the oil of Vibirnum opulus.
Bildiri - Yayımlanmış
Keywords: Eucalyptus; Vibirnum; Essential oil; Turkey